End‐stage renal disease patients undergoing angioplasty and bypass for critical limb ischemia have worse outcomes compared to non‐ESRD patients: Systematic review and meta‐analysis. Issue 2 (6th April 2021) - Dawson, Desireé B.; Telles‐Garcia, Nelson A.; Atkins, Jessica L.; Mina, George S.; Abreo, Adrian P.; Virk, Chiranjiv S.; Dominic, Paari S.
Abstract: Background: End‐stage renal disease (ESRD) is associated with increased morbidity and mortality following lower extremity amputation for critical limb ischemia (CLI). Angioplasty and bypass are used in ESRD patients with CLI; however, the treatment of choice remains controversial. We compared the long‐term outcomes in patients with CLI undergoing angioplasty or bypass to evaluate the differences between patients with ESRD and those without ESRD. Methods: Established databases were searched for observational studies comparing outcomes following bypass or angioplasty for CLI in patients with ESRD to those in non‐ESRD patients. End points included survival, limb salvage, amputation‐free survival (AFS), and primary and secondary patency at 1‐year post‐procedure. Pooled odds ratios (OR) with 95% confidence intervals (CI) were calculated using a random effect model. Results: We included 20 studies with a total of 24, 851 patients. ESRD patients compared to non‐ESRD patients with CLI had significantly lower survival post‐angioplasty (OR 0.51, 95% CI 0.36–0.72, p  < .001) and post‐bypass (OR 0.26, 95% CI 0.15–0.45, p  < .001). ESRD patients had lower rates of limb salvage post‐bypass (OR 0.33, 95% CI 0.21–0.53, p  < .001) and post‐angioplasty (OR 0.54, 95% CI 0.41–0.70, p  < .001). AFS was significantly lower in ESRD patients compared to non‐ESRD patients following angioplasty (OR 0.48, 95% CI 0.32–0.71, p  < .001) and bypass (OR 0.28, 95% CI 0.16–0.47, p  < .001) despite no significant differences in primary patency. ESRD patients had overall worse secondary patency post‐angioplasty and/or bypass (OR 0.54, 95% CI 0.32–0.94, p  = .03) compared to non‐ESRD patients. A meta‐analysis of four studies directly comparing survival in ESRD patients with CLI based on whether they underwent angioplasty or bypass showed no difference (OR 0.93, 95% CI 0.64–1.35, p  = .69). Conclusion: ESRD patients have worse survival, limb salvage, and AFS outcomes following angioplasty and bypass for CLI compared to non‐ESRD patients. Large randomized controlled trials comparing these two modalities of treatment in this patient population are needed for further clarity.